The Role of Job Satisfaction in Mediating the Influence of Motivation and Competence on Employee Performance at PT. Sriti Sakti Abadi in Denpasar - DIANINGSIH, Ni Wayan Yunita; SUGIATI , Gusti Ayu; LAKSMI, Putu Ayu Sita (PT Keberlanjutan Strategis Indonesia, 2025)
As a partner of PT. PLN (Persero), especially in the PLN Bali Distribution Unit, PT. Sriti Sakti Abadi is required always to provide maximum performance in electricity services. Human resources are the main asset in achieving this performance. This study aims to analyze work motivation and work competence on employee satisfaction and performance. Data were collected through a survey of 53 employees who were sampled in the study. The results of data collection were processed using Partial Least Squares Structural Equation Modeling. The results of the survey indicate that motivation has no significant effect on employee performance, motivation has a positive and significant effect on employee job satisfaction, competence has a positive and significant effect on employee performance, competence has a positive and significant effect on employee job satisfaction, job satisfaction has a positive and significant effect on employee performance, job satisfaction is unable to mediate the effect of motivation on employee performance, job satisfaction is unable to mediate the effect of competence on employee performance.